Social insecurity in the new millennium : the Central Provident Fund in Singapore - Low, Linda (Public administration & policy, 2004)
"The Central Provident Fund (CPF), which used to work for Singapore as a distinctive national social security and welfare protection scheme, has come up against myriad challenges in a world more volatile, uncertain, disruptive and risky than it was at the time of its inception. Without some form of redistribution, the CPF model has become inadequate in the provision of social welfare safety and protection." "The aim of the book is to review the origin and evolution of the CPF and the role it plays in both the social security and political economy of Singapore. The authors maintain that the CPF is still a cornerstone in the growth and development of Singapore, and that even though it is past its "golden age", the next page in its history can still be illustrious."--BOOK JACKET.